How Motivation, Compensation, and the Work Environment Maximizing Employee Performance? - Syahputra, Dimas Ramadhan; Faruqi, Faris (SAN Scientific, 2024)
This study aims to determine the effect of motivation, compensation, and work environment on employee performance. This study uses a quantitative research type, with an Associative research strategy. with data collection techniques using a questionnaire measured by a Likert scale. Data were analyzed by validity testing, reliability testing and Hypothesis Testing. The population in this study were all Coffee shop employees in Jakarta. The population in this study was 210 respondents with a 5% error rate determined by the SEM formula. Data collection was carried out by distributing questionnaires. The results of this study indicate that motivation affects employee performance, compensation affects employee performance because decent compensation improves employee performance, and the work environment also affects employee performance because the work environment is also very important for the comfort of employees to do the work given. The managerial implications of this study indicate that increasing motivation, compensation, and a conducive work environment can significantly improve employee performance. Managers need to consider better policies related to rewards, incentives, and creating a supportive work atmosphere to increase productivity. This can be done through motivational training programs, restructuring a fairer compensation system, and ensuring a comfortable and safe work environment